Die Stimme der Diotima: Friedrich Hölderlin und Luigi Nono - Allwardt, Ingrid (Berlin Kadmos, 2004)
Luigi Nono begins his score with a multi-layered preface, following a mysterious title: "Fragments - Silence, To Diotima". He adds further instructions to the musical notation system: how to read. Initially, there are no concrete technical instructions to be read, i.e. notes and performance instructions, but poetic words. Words that accompany the introduction to the composition with the request to its interpreters not to "sing" it audibly, but inwardly in words, not in notation, and to do so entirely "according to their self-understanding, according to the self-understanding of sounds". The words of a poet who composes in his own language, who writes entire "scores" himself: '"Fragmente aus Gedichten" by Friedrich Hölderlin, which revolve around the figure of Diotima. Both composer and poet stage the paradox of the voice, which simultaneously refers to what is absent, to what is not yet and no longer current, with everything it says and wants. (Translated with Deepl.com)
Includes bibliographical references (p. [187]-192).
Keywords: Nono, Luigi -- 1924-1990; Hölderlin, Friedrich -- 1770-1843; Composing; Poetry; Musical interpretation